1998
DOI: 10.1002/(sici)1521-3773(19980817)37:15<2110::aid-anie2110>3.0.co;2-k
|View full text |Cite
|
Sign up to set email alerts
|

Hexahelicenophanes and Their Racemization

Abstract: A drastic increase in the rate of racemization is found for the bridged hexahelicenophanes 1 (n=8, 10) relative to the unsubstituted parent [6]helicene. This unexpected result occurs from steric interactions between the polymethylenedioxy chains and the terminal rings, which causes the energy of the ground state to be raised and that of the transition state to be lowered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 4 publications
0
9
0
Order By: Relevance
“…81 The work of Meier and coworkers indicated that the macrocyclization can proceed in low to moderate yields (18-63%), but the photocyclization was more difficult (32-37% yield). 82,83 To conclude, the chiral tether strategy did not seem to improve the photocyclization yields to afford carbohelicenes, but it provided in one case, a very high diastereoselectivity (a single diastereoisomer detected).…”
Section: Asymmetric Photosynthesis With Chiral Inducers and Auxiliariesmentioning
confidence: 91%
“…81 The work of Meier and coworkers indicated that the macrocyclization can proceed in low to moderate yields (18-63%), but the photocyclization was more difficult (32-37% yield). 82,83 To conclude, the chiral tether strategy did not seem to improve the photocyclization yields to afford carbohelicenes, but it provided in one case, a very high diastereoselectivity (a single diastereoisomer detected).…”
Section: Asymmetric Photosynthesis With Chiral Inducers and Auxiliariesmentioning
confidence: 91%
“…1,n-Dioxa[n](4,13) [6]helicenophanes 155b-c were synthesized using a Type III approach, which culminated with the Mallory reaction of macrocycles 154b-c (Scheme 34). 101 Interestingly, the lower homolog 154a did not afford helicenophane 155a, but rather a dimer resembling 64 (Scheme 13). This enabled the determination of the racemization barriers (at 200 °C).…”
Section: Scheme 31mentioning
confidence: 99%
“…Compounds (I) and (II) were prepared according to the literature (Meier et al, 1998) and recrystallized from chloroform.…”
Section: Methodsmentioning
confidence: 99%
“…The steric energy, particularly that of (II), raises the energy of the ground states. In the transition states of the racemization of (I) and (II), the bridges are rotated, the C 2 symmetry of the molecules in solution being transformed to a C s symmetry (Meier et al, 1998), and the steric interactions between the hexahelicene moiety and the bridge are lowered. Thus, we conclude that the decreasing racemization barrier in going from [6]helicene to (I) to (II) is due to the increase of the steric energy in the ground states in this series whereas the transition states are less affected.…”
mentioning
confidence: 99%